DTPB as a Better Voluntary Tax Compliance Predictor - A Comparison Study - Derashid, Chek; Bidin, Zainol (Journal of Business Management and Accounting, 2020)
Tax administrators have been trying to maximise its voluntary tax compliance rate where e-filing system has been the preferable compliance tool by taxpayers in submitting their income tax return forms. Despite the effort to provide better services to taxpayers, the heterogeneous taxpayers in Malaysia face difficulties in extracting information and tax knowledge that would require assistance or advice from other sources, like their peers and mass media, while some may have financial difficulties. This comparative study proposes to utilise the multidimensional model of Decomposed Theory of Planned Behaviour (DTPB) that incorporates general tax knowledge, mass media referent, and ability to pay as addition to the original DTPB model. The findings showed that general tax filing knowledge, mass media referent, and ability to pay have significant influence on intention to comply with tax laws. However, perceived usefulness, perceived ease of use, compatibility, and self-efficacy were found to be not significant when the DTPB model was adopted. Nevertheless, it is advantageous to use the DTPB model that provides predictiveness and explanation toward understanding voluntary tax compliance behaviour. This model is useful as a guide for improving voluntary tax compliance rates while promoting the advantages of using e-filing system as the preferable tool for compliance.
Keywords: Voluntary tax compliance intention; theory of reasoned action (TRA); theory of planned behaviour (TPB); Decomposed Theory of Planned Behaviour (DTPB)